Optimalisasi Digitalisasi Arsip pada Kantor Mahkamah Syar’iyah - Juni Ahyar; Zamzami Zainuddin; Indra Maulana; Rudi Kurniawan (Sekolah Tinggi Ilmu Administrasi Nasional, 2021)
This study aims to determine the management of digital archives at the Syar'iyah Court Office of East Aceh Regency, Indonesia, as well as finding obstacles encountered in their implementation. This research is a qualitative analysis where the subjects of this research were officers who managed digital archives at the Syar'iyah Court office. The data collection techniques employed were interviews, observations, and documentation. The results of this study indicate that the management of digital archives at the Syar'iyah Court Office has not been implemented optimally due to three conditions, namely: 1) The creation of digital archives is hampered due to frequent power outages in East Aceh and Sarana districts which are less supportive, and lack of resources. employees who understand digital archiving issues; 2) The process of borrowing archives carried out at the Syar'iyah Court Office has not been going well because it has not used archive lending procedures such as requesting archives, searching, retrieval of archives, recording, controlling, and storing again, to prevent loss of records; 3) Archive rediscovery still takes quite a long time, ranging from 20 to 30 minutes. The management of digital archives at the Office of the Syar'iyah Idi Court of East Aceh Regency should be improved by proposing additional archiving facilities, namely the latest model scan tool and additional employees who handle digital archive issues.